Impact of Hypoglycemia on Health-Related Quality of Life among Type 2 Diabetes: A Cross-Sectional Study in Thailand - Thongchai Pratipanawatr; Bancha Satirapoj; Boonsong Ongphiphadhanakul; Sompongse Suwanwalaikorn; Wannee Nitiyanant (Journal of Diabetes Research)
Type 2 diabetes mellitus (T2DM) is one of the most common chronic diseases. Patients are generally advised lifestyle changes with antihyperglycemic agents prescribed. The major drawback of prescribing antihyperglycemic agents is the risk of hypoglycemia which subsequently impacts on health-related quality of life (HRQoL). This study is aimed at examining association between previous history of hypoglycemia and HRQoL. The study was a multicenter cross-sectional study, conducted from February 2013 to March 2015 at 5 tertiary care hospitals in Thailand (Srinagarind, Phramongkutklao, Ramathibodi, King Chulalongkorn Memorial, and Siriraj hospitals). The study population were males or females diagnosed with type 2 DM according to ADA criteria, 30 years of age or older, who had been treated with sulfonylurea (SU) monotherapy or SU and metformin combination for at least 6 months. Prespecified medical factors were extracted from medical records 12 months prior to patients’ enrolment. The experience of hypoglycemia questionnaire was used to collect and measure severity of hypoglycemia experienced during the previous 6 months. HRQoL was assessed using the 3-level version of EuroQol-5-dimension (EQ-5D-3L) and visual analogue scale (EQ-VAS) questionnaires. Of 659 eligible patients surveyed, 202 patients (30.65%) had experienced symptoms of hypoglycemia. HRQoL was significantly lower among patients reporting at least one of hypoglycemic symptoms, measured by EQ-VAS scores (mean±SD; 73.66±13.18, 73.56±15.10, or 68.93±14.76 vs. 77.01±13.02, one-way ANOVA; p=0.006) and EQ-5D-3L index scores (0.62±0.47, 0.68±0.38, or 0.58±0.51 vs. 0.79±0.31, one-way ANOVA; p<0.001) for mild, moderate, or severe/very severe hypoglycemic patients compared with patients without hypoglycemic symptoms. After adjusting for confounding factors in a multiple linear regression model, patients with hypoglycemic symptoms either mild, moderate, or severe/very severe demonstrated significantly higher impairment for EQ-VAS and EQ-5D indexes than those who did not experience hypoglycemic symptoms. In conclusion, our study showed decreased HRQoL determined by EQ-5D and EQ-VAS in patients reporting symptoms of hypoglycemia compared with patients not reporting hypoglycemic symptoms, relative to severity of hypoglycemia.